Investigating the impact of intellectual capital on organizational performance and knowledge management operations (case study: Hamedan county governor. - Mehdi Ajalli; Mohammadreza Alizadeghan (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The emergence of a new economy based on knowledge and information has increased researchers' interest in intellectual capital. This field, which has attracted the attention of many researchers, uses intellectual capital to determine the organisation's value. In the knowledge economy, unlike the industrial economy, knowledge or intellectual capital plays a significant role in generating wealth compared to other assets, gaining a competitive advantage, and advancing organizational goals. Knowledge management is the most valuable and strategic resource for organizations, and organizational performance is one of the critical steps in achieving success and excellence. The present study was conducted to investigate the impact of intellectual capital on organizational performance and knowledge management operations in the governorate of Hamedan city.Methodology: This research is practical in terms of purpose. The research method was descriptive of the correlation type, and the study's statistical population included all the employees of the Hamedan city governorate in 2022-2023, which consists of 65 people. In this research, using Morgan's table and considering the limited number of the statistical population, the number of research samples was selected as 56 people, and the sampling method is a simple random method. Also, the reliability of the questionnaires is confirmed using Cronbach's alpha coefficient and composite reliability. The path analysis method was used to analyze the research data using SPSS 26 and SmartPLS 4 software.Findings: The final results of the hypotheses test showed that intellectual capital does not significantly affect the organizational performance of Hamedan governorate employees; Intellectual capital has a significant effect on knowledge management operations of Hamedan governorate employees. The operation of knowledge management significantly affects the organizational performance of Hamadan governorate employees.Originality/Value: In the studied organization, intellectual capital did not significantly affect the performance of Hamadan governorate employees, but it did affect the organizational performance of employees through knowledge management operations. Therefore, it is necessary to plan to improve the status of knowledge management operations (knowledge sharing, knowledge creation and acquisition) in the Hamedan governorate.